IMPLEMENTASI SENSOR WARNA UNTUK SISTEM SORTIR DAN PENGISIAN BOTOL OTOMATIS BERBASIS PLC DAN ESP32 - Muharram Khadafi; Iskandar Lutfi; Johansyah Al Rasyid (PT. Hasba Edukasi Mandiri, 2025)
This research aims to develop an automated bottle filling and sorting system based on the TCS3200 color sensor, ESP32, and PLC. The system is designed to detect the label color of the bottle to determine the type of liquid to be filled either orange or lychee flavored drink and to automatically sort the bottles into the appropriate lanes. The automation process includes proximity sensors for bottle detection, a motor pump for liquid filling, and servo motors for sorting. Test results show that the system accurately detects colors and performs filling and sorting processes effectively, with a success rate of over 90%. However, some issues occurred in the capping and sorting stages due to mechanical or communication errors. This study demonstrates that the integration of ESP32, PLC, and color sensors offers an efficient and accurate solution for drink bottle production processes.